Director's Report - Stanton, D (My University, 2002)
With the focus of this edition of Family Matters being issues of work and family, the author makes reference to recent attention paid to work and family issues by the major Australian political parties, and notes that the Australian Institute of Family Studies is continuing its work in this area. He also provides information about two new projects for the Institute: the Stronger Families Learning Exchange, which forms part of the Government's Stronger Families and Communities Strategy; and the Longitudinal Study of Australian Children, which will examine the impact of Australia's unique social and cultural environment on the next generation, and explore family and social issues relevant to children's development.
Keywords: Surveys and Survey Methodology; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Surveys and Survey Methodology